USING THE BAND RATIO CLASSIFICATION METHOD TO DETECTTHE REGIONS THAT NEED TO REMOVE SEDIMENTATION INTIGRIS RIVER - Hadi, Gheidaa; Najeeb, Ahmed (Iraqi Journal of Science, 2024)
LandSat Satellite ETM+ image have been analyzed to detect the different depthsof regions inside the Tigris river in order to detect the regions that need to removesedimentation in Baghdad in Iraq Country. The scene consisted of six bands(without the thermal band),It was captured in March ٢٠٠١. The variance in depth isdetermined by applying the rationing technique on the bands ٣ and ٥.GIS ٩.١program is used to apply the rationing technique and determined the results.